The Second Reformation – an Ideology in Early Modern History? - Scheifele, Leopold (Senoji Lietuvos literatūra, 2018)
Darius Petkūnas, The Second Reformation in German-Speaking Lands. Monografija. Klaipėda: Klaipėdos universiteto leidykla, 2018, 702 p. ISBN 978-609-481-000-8.